The effect of PTH(1‐34) on fracture healing during different loading conditions. (18th September 2013) - Ellegaard, Maria; Kringelbach, Tina; Syberg, Susanne; Petersen, Solveig; Beck Jensen, Jens‐Erik; Brüel, Annemarie; Jørgensen, Niklas Rye; Schwarz, Peter
ABSTRACT: Parathyroid hormone (PTH) and PTH(1‐34) have been shown to promote bone healing in several animal studies. It is known that the mechanical environment is important in fracture healing. Furthermore, PTH and mechanical loading has been suggested to have synergistic effects on intact bone. The aim of the present study was to investigate whether the effect of PTH(1‐34) on fracture healing in rats was influenced by reduced mechanical loading. For this purpose, we used female, 25‐week‐old ovariectomized rats. Animals were subjected to closed midshaft fracture of the right tibia 10 weeks after ovariectomy. Five days before fracture, half of the animals received Botulinum Toxin A injections in the muscles of the fractured leg to induce muscle paralysis (unloaded group), whereas the other half received saline injections (control group). For the following 8 weeks, half of the animals in each group received injections of hPTH(1‐34) (20 µg/kg/day) and the other half received vehicle treatment. Fracture healing was assessed by radiology, dual‐energy X‐ray absorptiometry (DXA), histology, and bone strength analysis. We found that unloading reduced callus area significantly, whereas no effects of PTH(1‐34) on callus area were seen in neither normally nor unloaded animals. PTH(1‐34) increased callus bone mineral density (BMD) and bone mineral content (BMC) significantly, whereas unloading decreased callus BMD and BMC significantly. PTH(1‐34) treatment increased bone volume of the callus in both unloaded and control animals. PTH(1‐34) treatment increased ultimate force of the fracture by 63% in both control and unloaded animals and no interaction of the two interventions could be detected. PTH(1‐34) was able to stimulate bone formation in normally loaded as well as unloaded intact bone. In conclusion, the study confirms the stimulatory effect of PTH(1‐34) on fracture healing, and our data suggest that PTH(1‐34) is able to promote fracture healing, as well as intact bone formation during conditions of reduced mechanical loading. © 2013 American Society for Bone and Mineral Research.